Rare polypoid gastric mucosa induced small bowel intussusception in a toddler - Brianna M. Bowman; Suy sen Hung Fong; Joel M. Prince; Subhasis Misra; Drew Rideout (Elsevier, 2022)
Intussusception is a relatively rare occurrence in the pediatric age group and is typically idiopathic. There are even rarer occurrences of intussusception due to heterotopic gastric mucosa with an incidence of 0.1-13%. Understanding the clinical presentation of intussusception and the potential causes is crucial for appropriate care and management. This is a case report of a pediatric patient who presented with small bowel obstruction due to intussusception from a heterotopic gastric polyp in the jejunum.